2019
DOI: 10.3329/jemc.v9i3.43246
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Spinal Anesthesia during Emergency Cesarean Section for Severe Preeclampsia and Eclampsia Patients in a Tertiary Care Hospital

Abstract: Background: In Bangladesh eclampsia and severe preeclampsia or toxemia (PET) are the leading cause of perinatal morbidity and mortality. Its management is challenging for the obstetrician and anesthesiologist. Still now general anesthesia is commonly practiced for emergency LUCS in developing countries, but the outcome of spinal anesthesia is better than GA. Recently in developed countries like the UK and United States, spinal anesthesia is also accepted as a safer anesthetic technique. Objective: The ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Regarding maternal outcomes, spinal anesthesia groups had higher ICU admission within 24 h but the difference was not statistically significant. Thus, there were no statistically significant differences regarding maternal outcomes at 24 h. Unlike this finding study by Ashrafu Islam et al demonstrated spinal anesthesia was associated with better maternal outcomes [ 30 ].…”
Section: Discussionmentioning
confidence: 51%
“…Regarding maternal outcomes, spinal anesthesia groups had higher ICU admission within 24 h but the difference was not statistically significant. Thus, there were no statistically significant differences regarding maternal outcomes at 24 h. Unlike this finding study by Ashrafu Islam et al demonstrated spinal anesthesia was associated with better maternal outcomes [ 30 ].…”
Section: Discussionmentioning
confidence: 51%